Exploring the Role of Knowledge Sharing in Enhancing Innovative Work Behavior in Small Medium-sized Industries - I Gede Rihayana; I Nengah Aristana (Journal of Economics, Business, and Accountancy Ventura, 2024)
This study investigates the impact of transformational leadership on innovative work behavior, with a focus on the mediating role of knowledge sharing. Data were collected through a questionnaire administered to 126 respondents from small and medium-sized export industries in Bali. The data were analyzed using SmartPLS 3.2.9. The findings indicate that transformational leadership has a significant effect on innovative work behavior. Furthermore, knowledge sharing serves as a mediator between transformational leadership and innovative work behavior. The study acknowledges limitations, such as potential bias from self-assessment methods. The implications suggest that leaders in small and medium-sized industries should gain a deeper understanding of the relationships between these variables and the mediating mechanisms involved. This information can be valuable for enhancing leadership performance and fostering innovative work behavior in these industries. Theoretically, this study contributes to the understanding of how leadership styles can enhance organizational behavior, particularly in promoting innovative work behavior.